A Randomized Crossover Clinical Trial of Sertraline for Intradialytic Hypotension (Iranian Journal of Kidney Diseases, 2015)
Introduction. Intradialytic hypotension (IDH) has been reported in 15% to 50% of hemodialysis patients and increases patients morbidity and mortality. Some small noncontrolled studies evaluated the effect of sertraline on IDH with conflicting results. This study is a randomized crossover controlled trial on the effectiveness of sertraline to reduce IDH. Materials and Methods. Patients on hemodialysis who suffered IDH in at least 50% of their dialysis sessions were enrolled. Each patient received either sertraline or placebo for 4 weeks and after a 4-week washout period, was switched to the other arm of the trial. All patients started sertraline at a daily dose of 50 mg that increased to 100 mg after 1 week. Results. Twelve patients completed all phases of the study. Sertraline therapy increased nadir intradialysis diastolic and systolic blood pressure by 3.8 mm Hg and 4.9 mm Hg at the end of the intervention, respectively. Sertraline therapy also significantly increased postdialysis diastolic and systolic blood pressure by 6.0 mm Hg and 8.7 mm Hg. Sertraline therapy significantly reduced the risk of hypotension episodes by 43%. The improvement of intradialysis and postdialysis diastolic and systolic blood pressure were only significant in nondiabetic patients. Conclusions. Sertraline therapy significantly increases intradialysis and postdialysis blood pressure. These effects of sertraline can result in significant decrease in hypotension episodes during dialysis treatment and the number of interventions required to manage IDH. However, not all patients may benefit from sertraline depending on comorbidities such as diabetes mellitus.